Post-Course Evaluation of an Intensive Arabic Program: Students’ Perceptions of Its Impact on Speaking Proficiency / Taqyeem Ma Ba’da ad-Dawrah li Barnamaj al-Lughah al-Arabiyyah al-Mukaththaf: Tasawwurat at-Thullab hawla Atsarihi fi Tahsin al-Kafa’ah al-Shafawiyyah - Aaqil, Abdul Majeed Mohammed; Zunoomy, Muhammadu Sainulabdeen; Shibly, Firthouse Hassan Ahamed; Hamzah, Hamzah; Mahmud, Basri (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
Language plays a vital role in communication and consists of four main skills: reading, writing, listening, and speaking. Proficiency in these skills ensures fluency, and several factors—particularly intensive courses—contribute to its development. This study aims to evaluate the impact of an intensive Arabic program on enhancing learners’ speaking proficiency. Primary data were collected through questionnaires distributed to 196 first-year students who completed an eight-week intensive program in the Department of Arabic Language during the 2021/2022 academic year, with 138 valid responses. Secondary data were obtained from books, research papers, and online sources. Qualitative and quantitative methods were applied to analyze the data using MS Excel. The findings indicate that the intensive course significantly improved students’ speaking proficiency, along with their motivation, confidence, vocabulary, and interaction patterns. The study recommends implementing similar initiatives, such as Toastmaster and Gavel Clubs, to further enhance learners’ fluency inside and outside the university.مستخلص البحث: تلعب اللغة دورًا أساسيًا في عملية التواصل، إذ تتكوّن من أربع مهارات رئيسة هي القراءة والكتابة والاستماع والتحدث. وتمثّل الكفاءة في هذه المهارات أساس الطلاقة اللغوية، وتسهم الدورات المكثفة في تطويرها بفاعلية. يهدف هذا البحث إلى تقييم أثر برنامج اللغة العربية المكثف في تنمية الكفاءة الشفوية لدى المتعلمين. تم جمع البيانات الأولية عبر استبيان وُزّع على 196 من طلاب السنة الأولى الذين أتمّوا برنامجًا مكثفًا لمدة ثمانية أسابيع في قسم اللغة العربية خلال العام الأكاديمي 2021/2022، وتم استلام 138 استجابة. أما البيانات الثانوية فشملت الكتب والمقالات العلمية والمصادر الإلكترونية. استخدم المنهجان النوعي والكمي لتحليل البيانات بواسطة برنامج MS Excel. أظهرت النتائج أن الدورة المكثفة أسهمت في تحسين مهارة التحدث لدى الطلاب، إلى جانب تعزيز الثقة بالنفس والدافعية وتوسيع المفردات وتطوير أنماط التواصل. ويوصي البحث بتطبيق مبادرات مماثلة مثل أندية Toastmaster وGavel لتعزيز الطلاقة اللغوية داخل الجامعة وخارجها.